COGITO ERGO SUM : EXPLORATION OF RATIONALISM AND CERTAINTY IN THE CONSTRUCTION OF KNOWLEDGE - anggraini, Oci; Julita, Neli; Nafsih, Syarifatun (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2024)
This research conducts an in-depth exploration of Rene Descartes famous statement